2015
DOI: 10.1186/s13063-015-1022-5
|View full text |Cite
|
Sign up to set email alerts
|

Preventing anxiety problems in children with Cool Little Kids Online: study protocol for a randomised controlled trial

Abstract: BackgroundAnxiety disorders are the most common type of mental health problem and begin early in life. Early intervention to prevent anxiety problems in young children who are at risk has the potential for long-term impact. The ‘Cool Little Kids’ parenting group program was previously established to prevent anxiety disorders in young children at risk because of inhibited temperament. This group program was efficacious in two randomised controlled trials and has recently been adapted into an online format. ‘Coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…Full details of the study procedures are reported in the CLK trial protocol (Bayer et al, 2011) and the CLK-Online trial protocol (Morgan et al, 2015). In both trials, primary caregiving participants were recruited on the basis of a child score above 30 (approximately 1.15 standard deviations above the age-adjusted norm) on the Approach-Inhibition Subscale of the parent-report Short Temperament Scales for Children (Pedlow, Sanson, Prior, & Oberklaid, 1993;Prior, Smart, Sanson, & Oberklaid, 2000).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Full details of the study procedures are reported in the CLK trial protocol (Bayer et al, 2011) and the CLK-Online trial protocol (Morgan et al, 2015). In both trials, primary caregiving participants were recruited on the basis of a child score above 30 (approximately 1.15 standard deviations above the age-adjusted norm) on the Approach-Inhibition Subscale of the parent-report Short Temperament Scales for Children (Pedlow, Sanson, Prior, & Oberklaid, 1993;Prior, Smart, Sanson, & Oberklaid, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…The present study sample included 443 parents who completed 12-month follow-up assessments for a trial of the original group-based program (CLK; Bayer et al, 2011), and 341 parents who completed 24-week follow-up assessments for a trial of a new online adaptation of the group program (CLK-Online; Morgan et al, 2015). Follow-up data from the CLK and CLK-Online trials were used in the present study because this was the only time point to include the CALIS-PV and a diagnostic assessment of anxiety.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is online support for patients with other mental disorders that shows positive effects: for parents of children with autism spectrum disorders (Clifford & Minnes, 2013), for parents of socially anxious youth (Reuland & Teachman, 2014), for parents to prevent anxiety problems in young children (Morgan et al, 2015), and for bipolar parents of young children (Jones et al, 2015).…”
Section: Generalisabilitymentioning
confidence: 99%
“…Other studies bring evidence that iCBT treatments for children can be as effective as golden standards, i.e., face-to-face CBT delivered in a clinic [16]. Online-delivered CBT is also efficient in anxious preschool children, albeit it is delivered mostly as a parenting intervention [17,18].…”
Section: Internet-delivered Interventionsmentioning
confidence: 99%